Association Between Hypertension and Diabetic Ulcers in Diabetes Mellitus Patients - Evada, Alung Abhan; Pramana, Kadek Dwi; Wulandari, Made Ayu Mirah; Azhar, Mutiara Budi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
One of the most common diseases in the world, including in Indonesia, is diabetes mellitus, which can lead to complications such diabetic ulcers, which can raise the risk of death and amputation. It is believed that hypertension, as a risk factor in and of itself, contributes to the development of diabetic ulcers by causing both macrovascular and microvascular damage. This study aims to analyze the association between hypertension and diabetic ulcers in diabetes mellitus patients at the Mataram City Regional General Hospital (RSUD). This research is an analytical observational study with a case-control design. Sampling used purposive sampling technique. A total of 105 samples were selected with a 1:2 ratio between the case and control groups who met the inclusion and exclusion criteria. Data analysis was carried out using the Chi-Square test. There is a significant association between hypertension and diabetic ulcers (p-value = 0.028; OR = 2.771; 95% CI = 1.198–6.411). Subjects with uncontrolled hypertension were 3 times more at risk of developing diabetic ulcers.